The Cambridge Companion to British Fiction : 1980-2018 - Boxall, Peter (Singapore : Cambridge University Press, 2019)
"Introduction: Framing the Present Peter Boxall When does the present begin? An immediate answer to this curiously vexing question might be to suggest that the present does not begin. The present, one might argue, has no duration. It is the now, the passing moment, and as such cannot be truly said to have a beginning or an end, and cannot be measured, or regarded in any sense as having passed, or being to come. The present does not unfold or occur, but is the vanishing, fleeting medium of our immediate becoming"--
Introduction. Framing the present / Peter Boxall -- The 1980s / Bridget Chalk -- The 1990s / Pieter Vermeulen -- Post-millennial literature / Leigh Wilson -- British writing and the limits of the human / Gabriele Griffin -- Form and fiction, 1980-the present / Kevin Brazil -- Institutions of fiction / Caroline Wintersgill -- Late modernism, postmodernism, and after / Martin Eve -- Experiment and the genre novel / Caroline Edwards -- Transgression and experimentation: the historical novel / Jerome de Groot -- Film and fiction from 1980-the present / Petra Rau -- The Mid Atlantics / Ben Masters -- Fiction, religion and freedom of speech, from 'The Rushdie affair' to 7/7 / Stephen Morton -- Sexual dissidence and British writing / Rebecca Pohl -- British cosmopolitanism after 1980 / Patrick Deer -- Conclusion. Imagining the future / Peter Boxall.
Keywords: English Fiction -- History and Criticism; English Fiction -- History and Criticism